Intramolecular chaperone-mediated secretion of an Rhs effector toxin by a type VI secretion system - Tong-Tong Pei (Nature Portfolio, 2020)
Bacterial Rhs proteins with toxic domains are often secreted by type VI secretion systems. Here, the authors show that one of these proteins self-cleaves into three fragments, with the Rhs core and the N-terminal domain facilitating secretion and function of the C-terminal toxic domain.